Drivers of vulnerability to health and wellbeing challenges in informal settlements - Chumo, Ivy; Kabaria, Caroline; Shankland, Alex; Mberu, Blessing (Frontiers in Sustainable Cities, 2023)
It is widely acknowledged that vulnerable populations are hit very hard, both in the short and long term, when their health and wellbeing needs are not met. Despite the efforts at different levels to protect and promote their health and wellbeing, older persons, people with disabilities and children heads of households, continue to face significant social, economic and cultural difficulties in relation to health and wellbeing inequities. While rights to health and wellbeing are constitutionally guaranteed, and strategies can be advanced to reduce vulnerable situations, challenges persists and yet societies, communities, and individual factors that engender vulnerability are understudied and remain poorly understood. Situating our findings and understandings within CLUVA social vulnerability framework, allows us to adapt a conceptual framework for understanding vulnerability to health and wellbeing challenges across different groups in informal urban space. We used CLUVA social vulnerability framework to explore and uncover drivers of vulnerability to health and wellbeing challenges among the vulnerable and marginalized groups using the governance diaries approach. This was an ethnographic qualitative study, using governance diaries with 24 participants from Korogocho and Viwandani informal settlements in Nairobi, Kenya. The governance diaries approach involved bi-weekly governance in-depth interviews (IDIs) with study participants for 4 months, complemented with observations, reflections, participant diaries and informal discussions. Using content analysis methodology, we identified several interlinked drivers and grouped them as individual, community, societal and structural level factors. A comprehensive view of drivers at different levels will help actors engage in more expansive and collaborative thinking about strategies that can effectively reduce health and wellbeing challenges. These factors all come together to shape functioning and capabilities in informal settlements.